Translation Choices on the Word Level : And Their Effect on Understandability - Järvenpää, Jenna (My University, 2025)
In this thesis I look at how changes in translations can affect how the text is understood by the reader. The material that I analyse is Rick Riordan’s The Lightning Thief, and specifically Grover’s lines of dialogue in chapters 11 and 12. This analysis is done between the original English version and its Finnish translation. In order to do this analysis, I have used the theory of semantic translation and looked at what happens when it is not followed, as well as other theories about equivalence and translating literature. Based on my research, semantic translation is a type of translation that conveys meanings within a text and stays as true to the original as possible on all levels. Equivalence based on my research is defined as a similarity and comparability between the original and translated text. In addition to these I utilise theories that discuss other concepts of translation equivalence and the translation of literature. My analysis found that when semantic translation is not followed, the translated text can be understood differently by the TL reader. Sometimes these changes help the reader understand these texts better by, for example, adding to the context of the text. Other times these changes can change the characterisation of a character, for example by making Grover seem more aggressive than he is in the original text or by continuously referring to Medusa with either words that can be seen as degrading or with pronouns that are used to refer to animals and inanimate objects. Thus, I conclude that changes in translations do change how a text is understood.
Keywords: translation, equivalence, sematic translation, translation of dialogue, translation of children’s literature, translation choices, Rick Riordan, Percy Jackson